Fossil Energy Information Resources in the U. S. - Vaden, William M. (Journal of Information and Knowledge, 1977)
Information on fossil fuels and fossil energy technology is available through (1) U.S. Government organizations such as the Energy Research and Development Administration (ERDA) and Departments of Transportation and Interior, (2) state governments and their extensions such as Pennsylvania State University of Oklahoma, and (3) privately financed organizations such as the American Petroleum Institute and Engineering Index, Inc. Those information resource areas provide either generalized information for widespread public consumption of specialized information for specific segments of the fossil energy community, e.g, coal geologists and -chemists, petroleum engineers, and combustion and transportation engineers. ERDA is collecting and machine storing in one common bibliographic format worldwide information covering all areas of fossil energy with particular emphasis on coal and coal product technology.